Effect of Pre-Treatments and Polyethylene Packaging on Overall Chemical Constituents Such as Sugars and Organoleptic Parameters like Colour, Texture, Taste and Flavour of Chaunsa White Variety of Mango During Storage - Rathore, Habib Ahmed; Masud, Tariq; Sammi, Shehla; Soomro, Eijaz Hussain (Pakistan Journal of Nutrition, 2009)
Polyethylene packaging and Pre-treatments had significant effect (p<0.05) on overall chemical constituents such as reducing and non-reducing sugars (RS, TIS, SUC) Total Sugars (TS), Sugar Acid Ratio (SAR) and other organoleptic parameters like; Skin Color (SKC), Flesh Color (FLC), Texture (TEX), Taste (TAS) and Flavour (FLA) of Chaunsa white variety of mango fruit at ambient temperature (28-33oC and 56.7- 69.7% relative humidity) during storage. It was investigated that fruit treated with coating emulsions having fungicide, ethylene absorbent and antiripening agent, packed in polyethylene had lower RS ranged from (8.35-10.70%), TIS (17.78-24.66), SUC (9.07-13.75), TS (17.31-23.93), SAR value (25.31-39.79), lower SKC (.3.83-4.88), FLC (3.84-4.50), TEX (5.05-5.68), TAS (3.21-4.28) and FLA (3.74-4.76) with an average mean of 9.07%, 20.95%, 10.80%, 20.06%, 26.31, 3.93, 4.08, 5.20, 3.70 and 4.09 respectively at ambient temperature during 30 days of storage. The coated fruit packed in polyethylene had longer shelf life, minimum quality loss and slower increase in RS, TIS, SUC, TS contents, SAR, or lower score of SKC, FLC, TAS, higher TEX and slower increase of FLA respectively of fruit during storage. Whereas, the control sample had greater compositional changes with maximum quality loss, higher RS (9.67%), TIS (28.51%), SUC (19.83%), TS (29.38%), SAR (103.60), SKC (5.82), FLC (4.56), TAS (4.67), FLA (4.81) and lower TEX (4.98) and fruit was unacceptable after 12 days of their storage due to its unattractive skin, brown pulp color and poor taste.